Peran Koperasi Dalam Meningkatkan Perekonomian Pondok Pesantren Izzatuna Putra Palembang Dalam Perspektif Ekonomi Syariah - Mgs Muhammad Nur Ramadhan; Hilda Hilda; M. Iqbal (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
In the economic field, cooperatives are a form of cooperation in the economic sector. People believe in this collaboration because their lives share some of the same needs. One of the Islamic Boarding School Owned Enterprises (BUMP) at the Izzatuna Putra Palembang Islamic Boarding School is a pesantren cooperative that works to support the economy and improve the economy. This study aims to: (1) Describe the extent to which Islamic boarding school cooperatives have contributed to the economic expansion of Islamic boarding schools., (2) What is the role of cooperatives in improving the economy of the Islamic boarding school Izzatuna Putra Palembang in the study of Islamic economics. This is a type of field research using primary and secondary data sources. The data obtained will be presented with narrative text. This study uses qualitative data analysis methods/techniques using inductive thinking methods. The results of this study indicate that: (1) The role of cooperatives in improving the Islamic boarding school's economy is marked by the development of cooperatives that run a trading business every day where a portion of the profits will be deposited to the Islamic boarding school, both material and non-material, and the Islamic boarding school cooperative is also very helpful. in increasing the income of members of the cooperative and the Islamic boarding school community. (2) Then the role of the Izzatuna Putra Palembang Islamic Boarding School Cooperative in improving the economy of the Izzatuna Putra Palembang Islamic Boarding School in an Islamic perspective is carried out in several ways, namely: sharia economic values ​​in helping the community's economy, and avoiding incompatibility of sharia economic principles.